Relationship between Helicobacter pylori infection and GERD - Scida, Serena; Russo, Michele; Miraglia, Chiara; Leandro, Gioacchino; Franzoni, Lorella; Meschi, Tiziana; de' Angelis, Gian Luigi; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Gastroesophageal reflux disease (GERD) is due to the chronic exposure of the esophageal mucosa to acid secretion from the stomach. Helicobacter pylori (H.p.) infection, is a risk factor for the development of peptic ulcer, atrophic gastritis and gastric cancer, and causes various effects on gastric function. The relationship between GERD and H.pylori infection is still subject of debate. Background and aim: In literature no clear causal relationship has been established between GERD and H. pylori infection, although some papers support the onset of esophagitis in patients in whom the infection has been cured. Aim of this work is to review the most recent literature data about the relationship between reflux disease and H. pylori infection. Methods: Articles reviewed were found through literature searches on PubMed, Google Scholar using keywords such as gastroesophageal reflux disease, Helicobacter pylori, acid-related disorders, GERD and esophagitis